2017
DOI: 10.14392/asaa.2017100107
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Quality Attributes and Investment Opportunities for Latin American Firms

Abstract: This work verifies if companies with better accounting information show better performance and investigates the impact of better accounting information on the financial constraints. This study is based on an unbalanced panel data of 596 firms from seven Latin American countries between 1989 and 2009. The return on equity (ROE) and Market to book (MB) variables are used to define the firms' performance, which are regressed against five models that consider the quality of accounting information. We also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…Moreover, Sri Lanka is a country that mostly relies on tourism, and the selected sectors are more crucial to the development of Sri Lanka, which creates knowledge for the decision-makers at large. Accordance with prior studies (Shabeeb Ali et al, 2020;Carvalho et al, 2017;Habbash, 2012;Wijesinghe & Kehelwalathenna, 2017) we excluded the Banks, finance and insurance sector companies due to the peculiar nature of the sector. Also, we disregarded the diversified sector from our analysis due to the nonavailability of data due to the nature of the variable that we used in our study.…”
Section: Methodology Sample Data Data Collection and Data Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Sri Lanka is a country that mostly relies on tourism, and the selected sectors are more crucial to the development of Sri Lanka, which creates knowledge for the decision-makers at large. Accordance with prior studies (Shabeeb Ali et al, 2020;Carvalho et al, 2017;Habbash, 2012;Wijesinghe & Kehelwalathenna, 2017) we excluded the Banks, finance and insurance sector companies due to the peculiar nature of the sector. Also, we disregarded the diversified sector from our analysis due to the nonavailability of data due to the nature of the variable that we used in our study.…”
Section: Methodology Sample Data Data Collection and Data Analysismentioning
confidence: 98%
“…Stakeholders, especially investors, lenders, and managers, access information regarding companies through financial statements (Carvalho et al, 2017;Amr et al, 2019;Mayer, 2007). The International Accounting Standard Board (IASB) also recognised the importance of financial statements for investors' economic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Kordestani et al (2016) proved that the timely loss recognition did not affect the persistence and the predictive ability of earnings in Iranian listed companies during the period of 2003-2010, which implied that accounting conservatism did not distort earnings quality. Carvalho, Camargo and Kalatzis (2017) suggested that earnings quality attributes, including earnings predictive ability, were good explicators of operational and market performance of Latin American companies over the period of 1989-2009. Kundu and Banerjee (2021) suggested that Indian listed companies that reported better earnings in terms of predictive ability generated higher stock returns.…”
Section: __________________________________________________________________________ 2021 / 35mentioning
confidence: 99%
“…Earnings Quality, ou qualidade dos resultados contábeis (ou dos lucros), é um conceito que envolve indicadores que refletem o desempenho financeiro e informacional, atual e futuro, de determinada entidade, a partir de dados relevantes para a tomada de decisão, os quais são mensurados pela Contabilidade em um contexto específico (Carvalho, Camargo, & Kalatzis, 2017;Dechow et al, 2010). As medidas de qualidade dos lucros são estimadas a partir de relatórios anuais ou trimestrais, não sendo aplicadas em intervalos curtos, o que permite uma análise comparativa de dados recentes e anteriores (Ecker, Francis, Kim, Olsson, & Schipper, 2008).…”
Section: Earnings Qualityunclassified
“…Em suma, pode-se concluir que Earnings Quality é uma medida que possibilita a análise do desempenho operacional e de mercado de uma determinada entidade, o que implica diretamente no âmbito dos investimentos (Carvalho et al, 2017). Contudo, são várias as medidas que são utilizadas para mensuração da qualidade dos resultados, o que pode depender do momento, do cenário e das necessidades empresariais.…”
Section: Earnings Qualityunclassified